Democracy-affirming technologies: Aligning Technology with Public Interest and Social Good - Barker, Tyson; Blázquez Navarro, Irene; Braw, Elisabeth (IE Center for the Governance of Change, 2023)
This report is an integral component of Tech4Democracy, a global initiative led by IE University in partnership with the U.S. Department of State that was incorporated into The Summit(s) for Democracy launched in 2021 by President Biden. The initiative showcased its achievements in March 2023 at the Second Summit for Democracy in Washington, DC.
Keywords: Technology; Public Interest; Social Good